Catalytic hydroprocessing of fast pyrolysis oils: Impact of biomass feedstock on process efficiency. (January 2017) - Carpenter, Daniel; Westover, Tyler; Howe, Daniel; Deutch, Steve; Starace, Anne; Emerson, Rachel; Hernandez, Sergio; Santosa, Daniel; Lukins, Craig; Kutnyakov, Igor
Abstract: We report here on an experimental study to produce refinery-ready fuel blendstocks via catalytic hydrodeoxygenation (upgrading) of pyrolysis oil using several biomass feedstocks and various blends. Blends were tested along with the pure materials to determine the effect of blending on product yields and qualities. Within experimental error, oil yields from fast pyrolysis and upgrading are shown to be linear functions of the blend components. Switchgrass exhibited lower fast pyrolysis and upgrading yields than the woody samples, which included clean pine, oriented strand board (OSB), and a mix of piñon and juniper (PJ). The notable exception was PJ, for which the poor upgrading yield of 18% was likely associated with the very high viscosity of the PJ fast pyrolysis oil (947 cp). The highest fast pyrolysis yield (54% dry basis) was obtained from clean pine, while the highest upgrading yield (50%) was obtained from a blend of 80% clean pine and 20% OSB (CP8 OSB2 ). For switchgrass, reducing the fast pyrolysis temperature to 450 °C resulted in a significant increase to the pyrolysis oil yield and reduced hydrogen consumption during hydrotreating, but did not directly affect the hydrotreating oil yield. The water content of fast pyrolysis oils was also observed to increase linearly with the summed content of potassium and sodium, ranging from 21% for clean pine to 37% for switchgrass. Multiple linear regression models demonstrate that fast pyrolysis is strongly dependent upon the contents of lignin and volatile matter as well as the sum of potassium and sodium. Highlights: Various feedstocks were subjected to fast pyrolysis and hydrotreating to fuels. Mass yields, carbon-to-fuel efficiencies, and energy efficiencies are reported. Fast pyrolysis oil yields from blends were linear functions of components. A lower switchgrass pyrolysis temperature improved yields, reduced H2 consumption. A preliminary multivariate model to predict pyrolysis yields is presented.